2017
DOI: 10.1177/0148607117695251
|View full text |Cite
|
Sign up to set email alerts
|

When Is Parenteral Nutrition Appropriate?

Abstract: Parenteral nutrition (PN) represents one of the most notable achievements of modern medicine, serving as a therapeutic modality for all age groups across the healthcare continuum. PN offers a life-sustaining option when intestinal failure prevents adequate oral or enteral nutrition. However, providing nutrients by vein is an expensive form of nutrition support, and serious adverse events can occur. In an effort to provide clinical guidance regarding PN therapy, the Board of Directors of the American Society fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
202
0
9

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 180 publications
(235 citation statements)
references
References 388 publications
(581 reference statements)
1
202
0
9
Order By: Relevance
“…PN should not be initiated based on medical diagnosis or disease state alone, but instead a thorough evaluation including clinical factors and a physical examination should be completed to determine its appropriateness . For ICU patients who are determined to be severely malnourished or at high nutrition risk with an EN contraindication, guidelines suggest PN be initiated as soon as possible.…”
Section: Real or Perceived Intolerancementioning
confidence: 99%
See 1 more Smart Citation
“…PN should not be initiated based on medical diagnosis or disease state alone, but instead a thorough evaluation including clinical factors and a physical examination should be completed to determine its appropriateness . For ICU patients who are determined to be severely malnourished or at high nutrition risk with an EN contraindication, guidelines suggest PN be initiated as soon as possible.…”
Section: Real or Perceived Intolerancementioning
confidence: 99%
“…13,48 A meta‐analysis by Braunschweig et al showed no nutrition therapy in malnourished patients was associated with a significantly higher risk for mortality than exclusive PN (relative risk 3.0; 95% confidence interval, 1.09–8.56; P < .05). In well‐nourished or low nutrition risk ICU patients, exclusive PN can be withheld for the first 7 ICU days . However, supplemental PN (SPN) on day 7 can be considered for low or high nutrition risk patients not achieving at least 60% of energy and protein requirements through EN alone .…”
Section: Real or Perceived Intolerancementioning
confidence: 99%
“…PN should only be used in patients in whom the benefit outweighs the potential risks. In 2017, the American Society for Parenteral and Enteral Nutrition (ASPEN) published consensus recommendations on the appropriate use of PN . A 2013 ASPEN survey with a gap analysis revealed only 58% of healthcare organizations have precautions in place to prevent errors and patient harm associated with PN …”
mentioning
confidence: 99%
“…Parenteral nutrition (PN), conceived by Stanley Dudrick, Jonathan Rhoads, Douglas Wilmore, and Harry Vars >50 years ago, has significantly impacted the clinical care of patients, saving the lives of individuals who would otherwise have died because of severe malnutrition . Guidelines and recommendations for the use of PN have been described in documents from the American Society for Parenteral and Enteral Nutrition (ASPEN) and European Society for Clinical Nutrition and Metabolism (ESPEN) . Recent ASPEN consensus recommendations indicate that “an enduring debate about the role of intravenous nutrition in a variety of patient populations” exists .…”
mentioning
confidence: 99%